Mastering High Performance with Kotlin : Overcome Performance Difficulties in Kotlin with a Range of Exciting Techniques and Solutions. - Kucherenko, Igor (Packt Publishing Ltd, 2018)
A balance between implementing complex applications and optimizing performance is a present-day need. This book helps you achieve this balance while developing and deploying applications with Kotlin. You will learn how to use profiling tools to detect performance issues and discover bytecode that is generated to overcome performance bottlenecks.